AFTA DAN PENINGKATAN LIBERALISASI AKSES PASAR JASA KOREA DAN INDONESIA PADA MODA COMMERCIAL PRESENCE - Herlitah Herlitah (Fakultas Ekonomi Universitas Negeri Jakarta, 2017)
This study aims to measure the degree of liberalization of the services sector in Korea and Indonesia Mode 3(CommercialPresence)in the WTO and cooperation as well as test singnifikansi AKFTA improvement. The method used to measure the level of liberalization is Hoekman index and the average difference test with t-test was used for testing out sigfikansi increased liberalization between the two countries of the WTO to AKFTA. The results showed that Korea has been more liberal than in Indonesia on the second of this cooperation. In cooperation WTO, Korea open as many as 104 sub-sectors with an average level of liberalization of 0.53 (scale 1), while Indonesia only open as many as 56 sub-sectors with an average index of 0.18. In cooperation AKFTA, Korea increase the number of sub-sectors to 147 with price liberalization level of 0.76. The number of sub-sectors of Indonesia also increased to 72 with an average level of liberalization of 0.22. Increasing the number of sub-sectors and the level of liberalization of Korea and Indonesia from the WTO to AKFTA based on the t-statistic is significant at the 5% level. This means that both countries berliberalisasi significantly to liberalize the services sector. Keywords: Trade in Services, Improved Rate Liberalization, WTO, AKFTA